Effects of Exercise Training on Bone Health Parameters in Individuals With Obesity: A Systematic Review and Meta-Analysis - Zouhal, Hassane; Berro, Abdel Jalil; Kazwini, Sarah; Saeidi, Ayoub; Jayavel, Ayyappan; Clark, Cain C. T.; Hackney, Anthony C.; VanDusseldorp, Trisha A.; Ben Abderrahman, Abderraouf; El Hage, Rawad (Frontiers in Physiology, 2022)
Background: Osteoporosis causes bone fragility, increasing the risk of fractures. Evidence suggests a strong correlation between obesity and fracture risk. Physical training is known to enhance bone resistance and protect from fracture; however, its osteogenic effect in the presence of obesity remains unknown. Objective: We sought to evaluate the influence of exercise training on bone health indices in individuals with obesity. Methods: This systematic literature search was conducted using common electronic databases from inception - December 2019. The following key terms (and synonyms searched for by the MeSH database) were included and combined using the operators “AND”, “OR”, “NOT”: ((“body mass index” OR obesity OR obese OR overweight OR fat mass) AND (“bone mineral density” OR “bone mineral content” OR “peak bone mass” OR “mechanical loading” OR Osteoporosis OR “bone geometry” OR “bone resistance”) AND (“exercise training” OR “physical training” OR “strength training”, OR “resistance training” OR “aerobic training” OR “combined training”)). Results: After screening, 10 studies (889 initial records) were included in the final analysis (8 different countries, 263 participants). Two studies investigated males, six women, and two, both sexes. The training duration was at least eight weeks with 2-3 sessions/week. Physical training displayed a significant trivial impact on the whole body (WB) BMD (0.13 SMD; 95% CI [0.00, 0.26], p=0.046). Subgroup analyses indicated a significant small increase in the WB BMD (0.27 SMD; 95% CI [0.00, 0.53], p=0.048) in the endurance training group, a non-significant trivial increase in the WB BMD (0.11 SMD; 95% CI [-0.06, 0.29], p=0.203) in the resistance group, and a non-significant trivial increase in the WB BMD (0.03 SMD; 95% CI [-0.26, 0.32], p=0.86) in the combined training group. In addition, a significant small decrease was found in the weight of trained subjects (-0.24 SMD; 95% CI [-0.42, -0.05], p=0.011). Conclusion: Physical training has little to no effect on the WB BMD in subjects with overweight/obesity. Currently, insufficient evidence to advocate for any specific type of exercise for enhancing bone health exists for overweight/obese individuals. Investigations examining the impact of varying types of physical exercise on WB BMD of obese individuals are needed.